Mathematics Performance and Principal Effectiveness: A Case Study of Some Coastal Primary Schools in Sri Lanka - Egodawatte, Gunawardena (Alberta Journal of Educational Research, 2012)
This mixed method research study is situated in the school effectiveness research paradigm to examine the correlation between the effectiveness of urban, primary school principals and their students’ performance in mathematics. Nine, urban, primary schools from Negombo, a coastal fishing area in Sri Lanka, were selected; their student achievements in mathematics were documented in a longitudinal study from 1998 to 2002. At the end of 2002, principals in these schools were interviewed to obtain evidence of their effectiveness in six areas: (a) school vision, (b) decision-making process, (c) curriculum process, (d) staff development, (e) community relations, and (f) managing changes and challenges. The results indicate a measurable correlation between school performance and principal effectiveness. However, these results should be cautiously interpreted since there are other contextual factors that affect the functioning of these schools. The results also illustrate some challenges faced by principals in their day-to-day activities in coastal, primary schools in Sri Lanka. Cette recherche à méthodes mixtes se situe dans le paradigme de recherche sur l'efficacité scolaire pour examiner la corrélation entre l'efficacité des directeurs d'écoles primaires en milieu urbain et le rendement de leurs élèves en mathématiques. On a choisi neuf écoles primaires en milieu urbain à Negombo, une région du Sri Lanka où se pratique la pêche côtière et où le rendement des élèves en mathématiques avait été documenté dans une étude longitudinale de 1998 à 2002. À la fin 2002, on a passé en entrevue les directeurs de ces écoles pour obtenir des données sur leur efficacité dans six domaines: (a) la vision de l'école, (b) le processus décisionnel, (c) le processus impliquant le programme d'études, (d) le perfectionnement du personnel, (e) les relations avec la communauté et (f) la gestion des changements et des défis. Les résultats indiquent qu'il existe une corrélation mesurable entre le rendement scolaire et l'efficacité du directeur. Toutefois, il faudrait interpréter les résultats avec prudence compte tenu des autres facteurs contextuels qui affectent le fonctionnement de ces écoles. Les résultats illustrent également quelques uns des défis auxquels font face les directeurs au cours de leurs activités quotidiennes dans les écoles primaires de la côte du Sri Lanka.